An electro-deoxidation approach to co-converting antimony oxide/graphene oxide to antimony/graphene composite for sodium-ion battery anode. (1st February 2020) - Li, Xianyang; Qu, Jiakang; Xie, Hongwei; Song, Qiushi; Fu, Gaofeng; Yin, Huayi
Abstract: Low-cost and earth-abundant feedstocks and straightforward synthesis methods determine the practical application of metallic Sb-based anodes for sodium-ion batteries (SIBs). This paper aims to synthesize Sb/reduced graphene oxide (rGO) composite anodes by electrochemically reducing the mixture of Sb2 O3 and graphene oxide (GO) in strong alkaline solutions. Unlike the conventional way of preparing metallic Sb-based anode materials using SbCl3 or Sb, this paper employs Sb2 O3 and GO as feedstocks and electrons as the reducing agent. The strong alkaline solution suppresses the hydrogen evolution, and the GO reduces the IR drop and prevents the agglomeration of Sb particles. The electrolytic Sb/rGO composite delivers a high capacity of 584 mAh g −1 at 0.1A g −1 after 120 cycles. The superior battery performance of the Sb/rGO composite is attributed to the synergistic effect of the electrolytic Sb and rGO. Overall, the electrochemical deoxidation method can be applied for the preparation of other types of metal-carbon composites from the mixture of oxides and carbon materials.